PERILAKU SEKS PRANIKAH PADA MAHASISWA (Studi Kasus Mahasiswa UIN Suska Riau) - Amirah Diniaty (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2012)
Premarital sexual behavior is a sexual behavior without going through the formal process of marriage according to the law, religions and individual beliefs. It can be varied, such as feelings of attraction to the opposite sex, dating, flirting and sexual intercourse. The number of student who has sexual behavior before marriage, like icebergs on the surface of the sea, which seems just a bit, but essentially full of lumps. This is due to what she/he has done is outside monitoring of parents, faculty and the community. The results showed that the premarital sexual behavior always practiced by the respondents when they meet their partner are holding hands, kissing (dry and wet kisses) and flirting. There was a respondent who is always having sexual intercourse with his partner at least twice a week except when the patner has menstruation.